PENGARUH TINGKAT KEMANDIRIAN DALAM MEMENUHI KEBUTUHAN FISKAL DAERAH, TINGKAT KEMANDIRIAN DALAM MENGELOLA POTENSI DAERAH DAN SiLPA TERHADAP TINGKAT KINERJA PELAYANAN PUBLIK (Studi pada Pemerintah Daerah Kabupaten/ Kota di Jawa Tengah Tahun 2006 -2012) - Rofiqoh Kartikasari; Fuad Fuad (Diponegoro Journal of Accounting, 2014)
The aims of this research are to examine the influence of autonomy level to fulfill local fiscal’s need, to examine autonomy level to manage local potency and to examine the SiLPA to performaces level of local public service. Measurement used to measure autonomy level to fulfill local fiscal’s need by this research is proportion between PAD and DAU. While in terms of autonomy level to manage local potency, the measurement used is proportion between PAD and DBH. SiLPA in this research has no measurement since it is directly obtained from penerimaan pembiayaan. Whereas performance level of local public service as a dependent variable is measured by using proportion of capital expenditure and local expenditure.This research uses secondary data with population of all local governments in Indonesia which report its realizations of APBD in DJPK since 2006 until 2012. Purposive sampling is a method used in order to determine research’s sample. Whereas multiple regression is used as an analysis method.The result shows that autonomy level to fulfill local fiscal’s need (TKMKF) and autonomy level to manage local potency negatively (TKMP) affect performance level of local public service (TKPP) and the SiLPA positively affect performance level of public service (TKPP).